Libraries and librarians on Facebook : professional vs. personal involvment - Mučnjak, Dorja; Hebrang Grgić, Ivana (2012)
Since the launch of Facebook in 2004, it has become the most popular social networking site in the world. Libraries usually use the site with intention of meeting their patrons and promoting their services. When using Facebook, librarians have great ethical responsibility. One of the most important ethical issues is distinguishing between professional and personal attitudes. The first part of the paper is a short literature review. The second part is study of Croatian public libraries on Facebook. In the study, interests of Croatian libraries will be analysed. Librarians who administrate library pages or profiles can express interests by liking other Facebook pages or groups. How do they do that? Do they use the possibility for promoting their own political or religious views, their own music preferences, their favorite books and artists, or they are aware that as librarians they have to represent their library? In this article, we will try to answer these questions.
ENG